2002
DOI: 10.1641/0006-3568(2002)052[0019:lrsfes]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Lidar Remote Sensing for Ecosystem Studies

Abstract: Articlesface is repeatedly measured along a transect, the result is an outline of both the ground surface and any vegetation obscuring it. Even in areas with high vegetation cover, where most measurements will be returned from plant canopies, some measurements will be returned from the underlying ground surface, resulting in a highly accurate map of canopy height.Key differences among lidar sensors are related to the laser's wavelength, power, pulse duration and repetition rate, beam size and divergence angle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
891
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,477 publications
(907 citation statements)
references
References 44 publications
2
891
0
14
Order By: Relevance
“…Airborne light detection and ranging (LiDAR) is the state-of-the-art method for observing three-dimensional structural properties of forests at landscape spatial scales [8]. Of all vegetation metrics that can be derived from LiDAR datasets, forest height can be derived most consistently across sensor systems [9].…”
Section: Vegetation Metrics Derived From Lidar Datamentioning
confidence: 99%
“…Airborne light detection and ranging (LiDAR) is the state-of-the-art method for observing three-dimensional structural properties of forests at landscape spatial scales [8]. Of all vegetation metrics that can be derived from LiDAR datasets, forest height can be derived most consistently across sensor systems [9].…”
Section: Vegetation Metrics Derived From Lidar Datamentioning
confidence: 99%
“…Numerous studies 886 (Dubayah et al 2000, Lefsky et al 2002, Drake et al 2003, Hyde et al 2005) have 887 validated this approach. Additionally it is the foundation of the Tandem-L concept.…”
Section: Required Measurement Capabilities For Biomass 872 873mentioning
confidence: 99%
“…In addition to 908 canopy height, it has been shown that for lidar, other metrics are required for optimal 909 biomass estimation, such as HOME; these internal height quantiles should also be known 910 to about 10% relative to canopy height (Dubayah et al 2000, Lefsky et al 2002, Drake et 911 al. 2003, Hyde et al 2005 In certain regions of the world, especially in the tropics, forest biomass is known 916 to exceed 100 -200 Mg ha -1 .…”
Section: Required Measurement Capabilities For Biomass 872 873mentioning
confidence: 99%
“…However, we may not need to estimate all five parameters independently as crown radius is related to canopy height through allometry, and crown radius and stem density are constrained by canopy cover. Moreover, recent advances in remote sensing both with high spatial resolution optical sensors to extract LAI and tree crown size [Song and Dickinson, 2008;Song, 2007;Clark et al, 2004;Leckie et al, 2003] and with Lidar to extract canopy height [Lefsky et al, 2002;Sun et al, 2008] are making it possible to extract these canopy structural parameters as input to GCR.…”
Section: Discussionmentioning
confidence: 99%